Tips for making a movie. A learning object for autonomous learning - Rodrigues, Clarissa (2012)
The paper accounts for a developmental research in the area of courseware production for personal, and self-directed learning. A complete learning object was developed in the context of a master program in Technology and Digital Art. The aim is to make this course available through an online platform, using existing social networks to add social learning features. It is considered by the authors to be a kind of Personal Learning Environment, with a specific purpose.